Single and Especially Multisport Participation May Increase Physical Fitness in Younger Americans - Jenny Linker; Bradford Strand; Joe Deutsch; Seungmin Kang; Kelsey Slater; Alaina Driscoll; Ryan McGrath (MDPI AG, 2022)
Background: We sought to examine the associations between sports participation and physical fitness in younger Americans. Methods: The analytic sample included 1108 Americans aged 6-15 years. Muscular fitness assessments included handgrip strength, leg extension strength, and plank position. Cardiorespiratory fitness was examined with graded treadmill tests. Results: Youth participating in any sports had increased physical fitness performance for each marker: 1.63 kg (CI: 0.91-2.35) for handgrip strength, 6.23 kg (CI: 3.15-9.32) for leg extension strength, 9.41 lbs. (CI: 4.51-14.31) for plank position held, and 3.02 mL/kg/min (CI: 1.23-4.80) for estimated maximal oxygen uptake. Participants engaging in a single sport had increased performance for most fitness markers: 1.52 kg (CI: 0.67-2.38) for handgrip strength, 5.16 kg (CI: 1.50-8.82) for leg extension strength, 5.98 s (CI: 0.17-11.78) for plank position held, and 2.67 mL/kg/min (CI: 0.58-4.77) for estimated maximal oxygen uptake. Youth engaging in multiple sports exhibited even steeper trends: 1.77 kg (CI: 0.83-2.70) for handgrip strength, 7.63 kg (CI: 3.62-11.65) for leg extension strength, 13.89 s (CI: 7.52-20.27) for plank position held, and 3.50 mL/kg/min (CI: 1.15-5.85) for estimated maximal oxygen uptake. Conclusions: Any sports participation, including single and multiple sports, is linked to increased physical fitness in American youth.